Book Review of «Leibniz, el archifilósofo», by Javier Echeverría - Rubio Juan, María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Book Review of «Leibniz, el archifilósofo», by Javier Echeverría